Health literacy and health among the elderly: status and challenges in the context of the Polish population aging process - Słońska Zofia A.; Borowiec Agnieszka A.; Aranowska Anita E. (Anthropological Review, 2015)
Introduction: Poland is a country which is characterized by the process of population aging resulting in a dynamic growth of the old-age dependency ratio. Thus, along with the aging process, we can expect, both at the individual and at the societal level, the intensification of the problems related to coping with worsening health and social dependency of the growing number of the elderly. One of the most necessary action contributing to the prevention of the above-mentioned threats is the development of health literacy. Study aim: The aim of the study is to describe and analyze, in the context of the process of aging, the status, the structure and the role of health literacy among the elderly in Poland.